Improving Fourth-Grade Students’ Mathematics Learning Outcomes on Plane Shapes Through the Use of Animated Videos - Eka Filahanasari; Raimon Efendi; Anisa; Yulia Darniyanti; Suci Rahma Putri (Journal of Teaching and Learning Mathematics, 2026)
Mathematics learning on two-dimensional shapes in elementary schools is often hindered by the abstract nature of the material, whereas students aged 7–11 years are still operating within the concrete operational stage. This condition led to low learning outcomes among fourth-grade students at SDN 11 Sitiung, where baseline data showed that 66.67% of students had not achieved the minimum mastery standard due to the dominance of conventional teaching methods. This study aims to analyze the effectiveness of using animated video learning media in improving the mathematics learning outcomes of fourth-grade students regarding plane shapes. This research employed a field experimental method with a pre-experimental design, specifically the one-group pretest-posttest design. The population and sample consisted of all 18 fourth-grade students at SDN 11 Sitiung. The research data incuded questionnaires and written tests was  20-item multiple-choice test, which was verified as valid and reliable (α=0.855). Data were analyzed using the Shapiro-Wilk normality test and hypothesis testing via the Paired Sample T-Test using SPSS 27. The results indicated a significant improvement in learning outcomes following the intervention. The students' average score increased by 23.06, rising from 55.28 in the pretest to 78.33 in the posttest. Classical mastery also improved, with the number of passing students increasing from 4 to 12. The Paired Sample T-Test yielded a Sig. (2-tailed) value of 0.000, which is lower than the significance level of 0.05 (0.000 < 0.05), thereby rejecting H0 and accepting Ha. The use of animated video learning media has a significant effect on improving the mathematics learning outcomes of fourth-grade students regarding two-dimensional shapes at SDN 11 Sitiung. This audiovisual medium effectively bridges the gap between abstract concepts and concrete understanding while enhancing students' focus and active engagement in the learning process.